THE NIGER DELTA PHENOMENON FROM THE PERSPECTIVES OF SARTRE’S EXISTENTIALISM AND SOCIAL POSITIVISM - Ncha Gabriel Bubu (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
To some, existentialism and positivism in bipolar thinking, are dichotomies, others view them as related concepts in philosophy. It is a considered view of this paper that these two schools of thought are related, complementary and have a relationship that is useful in conflict resolution. This assertion is examined in this analysis vis-à-vis the Niger Delta, is the trust of this paper.